2022
DOI: 10.1186/s13256-022-03257-2
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic ischiofemoral impingement due to high tibial osteotomy with overvalgization: a case report

Abstract: Background Open wedge high tibial osteotomy is a standard procedure for frontal realignment. It is indicated in varus knee with reduced mechanical medial proximal tibia angle. Overcorrection producing a mechanical medial proximal tibia angle out of the normal range (85–90°) is not recommended because this would lead to unphysiological joint-line orientation. Osteotomies around the knee also influence the adjacent ankle and hip joints. For the hip, it is known that frontal alignment of the leg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The changes that occur at the ankle have previously been described but this is the first study to describe the relative changes that occur at the hip [ 8 , 9 , 10 , 12 ]. Palmer et al have described the increased incidence of CAM deformities in patients with a failing medial knee compartment and Konrads et al described a case of hip impingement after an HTO [ 5 , 6 ]. Further studies would prove beneficial in assessing the clinical significance of these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes that occur at the ankle have previously been described but this is the first study to describe the relative changes that occur at the hip [ 8 , 9 , 10 , 12 ]. Palmer et al have described the increased incidence of CAM deformities in patients with a failing medial knee compartment and Konrads et al described a case of hip impingement after an HTO [ 5 , 6 ]. Further studies would prove beneficial in assessing the clinical significance of these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of the hip in patients with knee malalignment have been made previously [ 5 ]. The current literature on the hip after MOHTO is limited to case reports [ 6 ]. Changes in the coronal alignment of the ankle after MOHTO have been studied in the past [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated earlier that the ischiofemoral distance measured on ap radiograph correlates with the real three-dimensional ischiofemoral distance measured on transverse CT slides [ 2 , 15 , 25 ]. Yet, it is reasonable to mention that therapeutic decisions and surgical indications should be based on measurements on transverse imaging slides (CT or MRI).…”
Section: Discussionmentioning
confidence: 98%
“…E.g., Ahmad et al demonstrated a correlation between the ischiofemoral distance (IFD) and the frontal alignment of the knee. Varisation osteotomy around the knee increases the hip abduction angle and thus the ischiofemoral space, which could correlate with extraarticular hip pain due to ischiofemoral impingement [1, 21]. Freiling et al described a correction of the mechanical femorotibial axis to a target between 0 and 3° depending on the extent of degenerative changes in the lateral compartment [15].…”
Section: Discussionmentioning
confidence: 99%